Lamotrigine in children with refractory epilepsy - Çelebi, Aslı; Yalnızoğlu, Dilek; Turanlı, Güzide; Topaloğlu, Haluk; Aysun, Sabiha; Topçu, Meral (The Turkish Journal of Pediatrics, 2008)
We studied the efficacy and side effect profile oflamotrigine (LTG) in children with intractable epilepsy. We reviewed the database of our prolonged video-EEG laboratory to screen patients with intractable epilepsy who were on LTG either alone or in combination for three months or more. Of 75 patients, 28 patients (37%) had primary generalized seizures, 42 patients (56%) had partial onset seizures with or without secondary generalization, and 5 patients (7%) had two or more types of seizures. LTG reduced seizure frequency by at least 50% in 57.1% of patients with partial seizures and in 53.6% of patients with primary generalized seizures. The incidence of adverse events was relatively low (15%); the most common was skin rash. LTG should be considered in the treatment of pediatric patients with both partial onset and primary generalized seizures refractory to the major older antiepileptic drugs. LTG has a favorable side effect profile.